A rapid onset of Guillain–Barre syndrome following spinal anesthesia for knee arthroscopy: a case report - Amin Ahmed Kapadia; Lena Koshy; Usman Ali; Salil Gupta; Hammad Naqi Khan (Journal of Medical Case Reports)
Abstract Background Guillain–Barré syndrome, a rare autoimmune polyneuropathy, typically follows infections and rarely surgical procedures. Post-surgical Guillain–Barré syndrome is an uncommon subset with significant clinical implications. Case presentation We report the case of a 76-year-old Middle Eastern (Bahrainian) male who developed Guillain–Barré syndrome immediately after undergoing routine knee arthroscopy under spinal anesthesia. Shortly postoperatively the patient developed urinary incontinence, followed by progressive bilateral lower limb weakness and sensory deficits. Neurological symptoms rapidly deteriorated by day two and urgent neurological evaluation was taken. Initial and repeat spinal magnetic resonance imaging showed no structural abnormalities, and cerebrospinal fluid analysis lacked albuminocytological dissociation, complicating diagnosis. Electrodiagnostic studies confirmed Guillain–Barré syndrome with demyelinating patterns. Treatment with intravenous immunoglobulin was initiated promptly, resulting in remarkable recovery. By discharge, the patient had regained full motor and sensory function and achieved complete recovery at 6 months follow-up. Conclusion This case highlights the challenges of diagnosing early post-surgical Guillain–Barré syndrome, which can present atypically and without classical cerebrospinal fluid findings. However, early recognition, multidisciplinary collaboration, and timely intravenous immunoglobulin therapy facilitated a favorable outcome. This report highlights the challenges of diagnosing early post-surgical Guillain–Barré syndrome and demonstrates the potential for complete recovery with prompt intervention, emphasizing the need for awareness and timely management in similar cases.